Efektivitas Algoritma Kruskal dalam Mengoptimalkan Jalur Terpendek pada Jaringan Intranet - Ar Ruhimat, Qurrota A'yuni; Slamin, Slamin; Malinda, Alvira (Puslitbang Sekawan Institute Nusa Tenggara, 2024)
This research takes a case study at the Communication and Information Service, Bondowoso Regency, which is one of the media for conveying information and connecting interactive communication between the government and the community. In the process of conveying information to the public, they utilize information technology, the Intranet Network. The problem found was that there were obstacles in ineffective cable installation. This relates to non-optimality in determining the shortest path between two points in an intranet network, and how to determine the correct wiring position, so that the amount used is minimal but can still function optimally and be connected to all computers. To overcome the problems above, in this research the Kruskal Algorithm will be applied which is one of the network optimization methods in Graph Theory. Graph Theory is one of fields in Mathematics that studies the relationships between objects and how these objects interact with each other. Meanwhile, the Kruskal algorithm is an algorithm used to find the shortest path between two points in a graph. It is hoped that this research can optimize the amount of cabling used in designing intranet network topologies so that we can design optimal intranet routes with minimal costs.